Karakterisasi Mortar Geopolimer terhadap Penambahan Kapur Berbasis Abu Terbang dan ASP dengan NaOH 10 Molar - Sibuea, Maria Enjelina; Wardhono, A. (Kadiri University, 2025)
Cement which is the main material for making concrete has a negative impact on environmental, namely producing carbon emissions. One alternative to overcome this, is the use of fly ash and rice husk ash as a cement substitute. The addition of lime, which is a form of CaO, functions to increase the reactive properties of class C fly ash. The concrete curing process is carried out at room temperature, because the properties of lime itself speed up the hardening process. This research aims to determine the best ratio for adding lime in terms of compressive strength, porosity and setting time. Lime was added with several variations, namely 1%, 2.5%, 5%, 7.5%, and 0% as a control. The results of this research on the addition of lime to geopolymer mortar are reducing the compressive strength value, increase porosity, and extends setting time. Mortar with 7.5% lime compared to 1% lime, has lower compressive strength (1.12 MPa: 7.70 MPa), higher porosity (32.91%: 18.72%), and longer setting time (270 minute: 240 minute). However, if mortar with 1% lime compared to normal gepolymer without lime, has better results. Higher compressive strength (7.70 MPa: 5.63 MPa), lower porosity (18.72%: 22.93%), and fast setting time (240 minute: 495 minute). So the results of this research, a slight change in the lime portion can make a significant difference, excessive additions will disrupt the geopolymer reaction.